2023
DOI: 10.1002/ijc.34495
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative FLOT plus ramucirumab for resectable esophagogastric adenocarcinoma: A randomized phase II/III trial of the German AIO and Italian GOIM

Abstract: This multicenter, randomized phase II/III study evaluated the addition of the vascular endothelial growth factor receptor‐2 inhibitor ramucirumab to FLOT as perioperative treatment for resectable esophagogastric adenocarcinoma. Patients received either FLOT alone (Arm A) or combined with ramucirumab followed by ramucirumab monotherapy (Arm B). The primary endpoint for the phase II portion was the pathological complete or subtotal response (pCR/pSR) rate. Baseline characteristics were comparable between both ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…In both the phase III RAINFALL study, which combined ramucirumab with cisplatin and fluoropyrimidine, 28 and the phase II RAINSTORM trial, which paired it with S‐1 and oxaliplatin, the combinations of ramucirumab and chemotherapy failed as first‐line treatments for AGC 29 . For the perioperative treatment of AGC, the addition of ramucirumab to the fluorouracil plus leucovorin, oxaliplatin, and docetaxel (FLOT) regimen did not lead to a statistically significant improvement in the pathological CR rate as compared with FLOT chemotherapy alone in the randomized phase II/III trial of the German AIO and Italian GOIM 30 . Another generally used anti‐angiogenic monoclonal antibody, bevacizumab, binds to VEGF‐A, thereby inhibiting VEGFR‐2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In both the phase III RAINFALL study, which combined ramucirumab with cisplatin and fluoropyrimidine, 28 and the phase II RAINSTORM trial, which paired it with S‐1 and oxaliplatin, the combinations of ramucirumab and chemotherapy failed as first‐line treatments for AGC 29 . For the perioperative treatment of AGC, the addition of ramucirumab to the fluorouracil plus leucovorin, oxaliplatin, and docetaxel (FLOT) regimen did not lead to a statistically significant improvement in the pathological CR rate as compared with FLOT chemotherapy alone in the randomized phase II/III trial of the German AIO and Italian GOIM 30 . Another generally used anti‐angiogenic monoclonal antibody, bevacizumab, binds to VEGF‐A, thereby inhibiting VEGFR‐2.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the combination of ramucirumab and paclitaxel was found to amplify paclitaxel's inhibitory effect on cell cycle progression and the suppression of VEGFR2 expression 35 . However, the failure of ramucirumab combined with FLOT chemotherapy for perioperative treatment of AGC indicated that the synergistic effect between ramucirumab and docetaxel remains questionable 30 . Such synergistic effect was also evident when apatinib was combined with a taxane and 5‐FU, as apatinib can bind to ABC transporters 15,19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On one hand, pCR is a known strong prognostic factor in GEA, 14 also exhibiting a potential association with overall survival (OS) in RCTs that compared two chemotherapy-containing treatments, as our informal illustration suggests (Fig 1). 9,13,[15][16][17][18][19][20][21][22] The magnitude of the difference in pCR (tumor regression grade 1a) rates in DANTE was comparable to that observed in the phase II portion of the FLOT4/AIO trial comparing FLOT versus ECF/X (D9% in DANTE v D10% in FLOT4/AIO), with the phase III portion of that study going on to demonstrate a significant benefit in both DFS (hazard ratio [HR], 0.75) and OS (HR, 0.77). 9,23 Moreover, the efficacy of immune checkpoint inhibition (ICI) is not limited to short-term responses, but can extend to the control or eradication of micrometastases in the longer term in GEA and other tumor types.…”
mentioning
confidence: 99%